BUILDING POLITE DA’WAH: ETHICS AND BOUNDARIES OF JOKING IN CONVEYING RELIGIOUS MESSAGES - M. Ibnu Naufal Maskuri (QAULAN: Journal of Islamic Communication, 2025)
The use of humor in da'wah has become increasingly common across various platforms such as sermons, social media, and podcasts, particularly in engaging younger audiences. While humor can enhance audience engagement, its use requires careful consideration to avoid diminishing the sacredness of religious messages or offending certain groups. This study aims to explore the ethical boundaries of humor in da'wah and its impact on the comprehension and acceptance of religious messages. Employing a literature review method, the study draws on the perspectives of religious scholars such as Imam Al-Ghazali and communication theorists like Marshall McLuhan. The findings indicate that humor, when aligned with Islamic values, can serve as an effective tool to build rapport between preachers and audiences. However, it is essential to maintain a balance between humor and the seriousness of da'wah to ensure the religious message remains clear and respectful. This study underscores the importance of using humor wisely to enhance the effectiveness of da'wah in an increasingly digital era. Keywords: Humor in Da'wah; Ethics of Joking; Religious Messages